Informatics - Editor, Editor (Journal of Engineering Education Transformations, 1994)
NBA for Quality Assuarance- A proposal to set up a National Board of Accreditaion (NBA) under AICTE to periodically conduct evaluation of technical institutions or programmes is reported to have been cleared. Accreditation shall be.. of an institution or a programme.